HPLC Determination and Comparative Analysis of Persistent Organic Compounds in Different Environmental Matrices - Khan, Nikhat; Ali, Maham; Yaqub, Ghazala; Sadiq, Zubi (Asian Journal of Chemistry, 2015)
The application of easy, low-cost and effective sample preparation approach for the determination of different categories of persistent organic compounds, fruit, vegetable, soil and water samples was conducted. After extraction of environmental matrices, targeted persistent residues of lufenron, imidacloprid, dimethomorph, paraquat, glyphosate, bifenthrin and difenoconazole were determined by the method validation of high performance liquid chromatography in the collected samples from the agricultural areas of Lahore and Rahim Yaar Khan, Pakistan. All fruits and vegetables were found to be contaminated with persistent organic compounds with the values exceeding maximum residue limits (MRLs) of Codex Alimentarius Commission. Present study is a contribution in scientific research that gives the comparative analysis of persistent organic compounds under various environmental conditions.